A cross‐cultural study of managerial skills and effectiveness. Issue 3 (2014) - Richard C. Hoffman; Frank M. Shipper; Jeanette A. Davy; Denise M. Rotondo
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this study is to examine the relationship between managerial skills and effectiveness in a cross‐cultural setting to determine their applicability. Design/methodology/approach – Data from 7, 606 managers in 5 countries from a large multinational firm were analyzed using structural equation modeling to assess all relationships simultaneously and reduce error effects. Findings – The results support the cross‐cultural validity of the model of managerial skills‐effectiveness. Few cross‐cultural differences were found. Interactive skills had greater positive impact on attitudes than initiating skills. Pressuring skills had a negative impact on attitudes. None of the skill sets were related to job performance. Research limitations/implications – Using a single firm and industry to control for other cultural levels may limit the generalizability of the results. Only three skill sets were assessed and one coarse‐grained measure of culture was used. These factors may account for the few cultural differences observed. Practical implications – Training programs for managers going overseas should develop both interactive and initiating skills sets, as both had a positive impact on attitudes across cultures. Originality/value – The model of managerial skills and effectiveness was validated across five cultures. The use of structural equation modeling ensures that the results are not an artifact of the measures and represents a more direct test for cross‐cultural differences. Managing successfully across cultures may require fewer unique skills, with more emphasis placed on using basic management skills having positive impact.